A comprehensive review of the role of immune checkpoint inhibitors in elderly patients affected by renal cell carcinoma. (September 2020) - Lolli, Cristian; Altavilla, Amelia; Conteduca, Vincenza; Farolfi, Alberto; Casadei, Chiara; Schepisi, Giuseppe; Banna, Giuseppe Luigi; De Giorgi, Ugo
Graphical abstract: Highlights: The treatment of elderly people affected by renal cell carcinoma is a common issue for oncologists in clinical practice. The number of older patients enrolled in pivotal trials of ICIs in RCC is low. Limited data show comparable outcomes of ICIs in elderly patients. ICIs do not seem to be more toxic in elderly than in younger patients with the limit of few data reported in clinical trials. Abstract: Background: Immune checkpoint inhibitors (ICIs) have been revolutionizing the treatment landscape of metastatic renal cell carcinoma (mRCC). The use of ICIs in elderly RCC patients has become a daily practice, although their real impact in elderly patients is nowadays not completely clarified. It has been hypothesized that ICIs might not perform as effectively in the elderly as in younger patients, likely because of the gradual deterioration of the immune system brought on by natural age advancement, namely immunosenescence. Methods: We reviewed all clinical trials with ICIs in mRCC focusing on efficacy and toxicity of elderly patients. Results: Among the 21 trials reviewed, only 5 of them provided data on elderly patients. With the limits of low accrual and events for elderly patients, the efficacy of ICIs in patients ≥ 65 years seems as relevant as for younger patients, but not reliable for patients ≥ 75 years, group with overall low number of events, both in pre- or previously untreated mRCC patients. These currently available data seem not to support the hypothesis of a lower efficacy of ICIs in elderly patients, at least for mRCC. These trials reported very few data about toxicities in the specific population of elderly patients. Conclusions: Although available data from clinical trials are poor, currently, they do not support the efficacy of ICIs is less in elderly mRCC patients.